(untitled) (BIRDEM Medical Journal, 2025)
Background: Hypospadias is one of the most common congenital abnormalities of the genitourinary tract in males. Its surgery has evolved with more than 150 procedures. Urethrocutaneous fistula continues to be most common complications regardless of location of meatus, procedure performed and experience of surgeon. Every effort goes to prevention of these complications. The surgical repair of hypospadias is done in two stages in a selected group of patients with severe anomaly. The first stage (stage I) procedure consists of correction of penile shaft curvature and second stage (stage II) repair involves the creation of a neourethra. This neourethra needs a cover of an intermediate layer in order to have good functional and cosmetic results. Aim of this study was to evaluate effectiveness of tunica vaginalis flap covering different hypospadias procedures with inference of significant decrease of urethra-cutaneous fistula rate. Methods: In this prospective study, we have managed 30 patients with severe hypospadias by staged repair from January, 2019 to December, 2023 at Department of Paediatric Surgery, BIRDEM General Hospital. In stage I, chordee correction was done by dividing the urethral plate and covering the penile shaft with dorsal prepucial flaps. In stage II, a neourethra was created and covered with tunica vaginalis flap through the same incision. An indwelling catheter was kept for 14 days. Results: Twenty six (86.6%) patients had good functional and cosmetic outcome. One (3.3%) patient developed urethracutaneous fistula which needed correction later. External meatus was at subglanular level in 3 (10%) patients which was well accepted by guardian. Conclusion: Staged repair of severe hypospadias is valuable in selected group of patients and tunica vaginalis flap is an excellent intermediate layer to cover the neourethra to prevent fistula and contracture. BIRDEM Med J 2025; 15(3): 125-130